Palynological Characterization of Four Varieties of Vigna unguiculata (L. WALP) and Its Taxonomic Significance - O.F.Akinyemi, P. H. Bashiru, A.S. Oyelakin, O.O.Fawibe (South Eastern European Journal of Public Health, 2025)
This study examined the pollen morphology of four varieties of Vigna unguiculata (cowpea), an important staple legume for food security in Nigeria and Africa. Knowledge of pollen characteristics can inform efforts to conserve crop genetic variation, crucial for developing resilient food production systems. The main objective was to differentiate these Vigna varieties based on their pollen morphology. Pollen samples were collected from four cowpea varieties (BBT Brown, IFE BPC, BBT White, and IFE Brown) grown in a screen house and analysed using standard palynological method. Statistical analysis was done using SPSS version 27.0. Pollen characters analyzed included polar and equatorial views, pore length, muri length, exine thickness and lumina width. Results showed statistically significant differences in all quantitative pollen characters among the four varieties (p<0.5). Key distinguishing features included reticulation pattern, pollen size, lumina size, presence of small columellate structures within lumina, and rounded features surrounding the pores. In conclusion, the pollen morphology of the four Vigna unguiculata varieties examined was quite distinct, allowing for their separation and identification. This knowledge can contribute to conservation efforts targeting the genetic variation and taxonomic classification of this important food crop, supporting sustainable development and food security.